UPAYA MENINGKATKAN PRESTASI DAN MOTIVASI BELAJAR MATEMATIKA MELALUI PEMBELAJARAN KOOPERATIF - Cicik Minarni (MEDIA DIDAKTIKA, 2021)
The purpose of this class action research is to improve the ability of students in Class IV II semester 2017/2018 academic year SD Negeri Sidorejo II, Sugio Subdistrict, Lamongan Regency in comparing fractions through cooperative learning assisted by concrete objects. This study uses action research as much as two cycles. Each cycle consists of four stages, namely: planning, implementation, observation, and reflection. The target of this study was fourth grade students of SDN Sidorejo II Sugio District, Lamongan Regency 2017/2018 Academic Year. Data obtained in the form of formative test results and observation sheets of teaching and learning activities. The results of data analysis showed that student learning achievement had increased from cycle I to cycle II, namely the first cycle the average value reached 70 and the second cycle reached 79.17. Whereas learning completeness also increased from 66.7% in the first cycle to 91.67% in the second cycle.